Potential Role of WIP Family Genes in Drought Stress Response in Rubus idaeus - Xiangqian Gao; Guiyan Yang; Dapei Li; Muhong Xie; Yujie Mei; Lan Hu; Yongqi Zheng; Evangelia V. Avramidou (Agriculture)
Rubus idaeus is one of the primary cultivated species of raspberries, renowned for its appealing color, distinctive flavor and numerous health benefits. WIP proteins, which contain three conserved amino acids (W: Tryptophan, I: Isoleucine, P: Proline) and four zinc finger motifs in a highly conserved C-terminal region, are members of the A1d subgroup of C2H2 zinc finger proteins. Drought is one of the main limiting factors of plant growth and development, which restricts the cultivation and utilization of raspberry in northwest China. In this study, to obtain candidate genes for drought resistance, we identified key related genes, RiWIPs, from R. idaeus and analyzed their bioinformation and tissue stress response expression to drought. We found that there are three RiWIPs in R. idaeus and they are located on chromosomes 3, 4 and 6 of R. idaeus, respectively. The open reading frames (ORFs) of the RiWIPs ranged from 870 to 1056 bp in length, encoding 289 to 372 amino acid residues. The proteins were highly conserved and feature diverse conserved motifs. The promoters of the RiWIPs contained abundant cis-elements related to growth, development and stress response. Tissue-specific expression analysis revealed that the RiWIPs were expressed in the leaves, stems and roots of both drought-susceptible and drought-tolerant cultivars, except for RiWIP2, which was only expressed in the roots of the drought-tolerant one. Under drought stress, the transcriptional activity of the RiWIPs was increased to different degrees with specificity in the leaves, stems and roots. Our study demonstrated the role of WIP genes in raspberry drought response and provided a marker gene, RiWIP2, for drought resistance and candidate genes for subsequent drought-resistant breeding of R. idaeus.